1996
DOI: 10.1021/np9601622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polygonum hydropiper Sulfated Flavonoids on Lens Aldose Reductase and Related Enzymes

Abstract: The sulfated flavonoids in Polygonum hydropiper showed potent inhibiton against lens aldose reductase. Among these flavonoids isorhamnetin 3,7-disulfate (5) was most potent. Kinetic analysis showed that 5 exhibited noncompetitive inhibition against both dl-glyceraldehyde and NADPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…It has been acknowledged that plant-derived extracts and phytochemicals are potential alternatives to synthetic inhibitors against AR. 19,23,27) Currently, the compounds isolated from plants as AR inhibitors are classified as flavonoids, [19][20][21][22][23][24][25][26] stilbenes, 19) terpenoids, 21) ellagic acid and its derivatives, 28) and alkaloids. The present study was carried out in a search for new potential AR inhibitors from the fruiting bodies of G. applanatum, and cerebrosides (3), 2,5-dihydroxybenzoic acid (6) and protocatechualdehyde (7) were isolated as active principles which may be useful for the treatment of diabetic complications.…”
Section: Resultsmentioning
confidence: 99%
“…It has been acknowledged that plant-derived extracts and phytochemicals are potential alternatives to synthetic inhibitors against AR. 19,23,27) Currently, the compounds isolated from plants as AR inhibitors are classified as flavonoids, [19][20][21][22][23][24][25][26] stilbenes, 19) terpenoids, 21) ellagic acid and its derivatives, 28) and alkaloids. The present study was carried out in a search for new potential AR inhibitors from the fruiting bodies of G. applanatum, and cerebrosides (3), 2,5-dihydroxybenzoic acid (6) and protocatechualdehyde (7) were isolated as active principles which may be useful for the treatment of diabetic complications.…”
Section: Resultsmentioning
confidence: 99%
“…Monoterpene glycosides, perillosides A and C isolated from the leaves of Perilla frutescens were found to be excellent aldose reductase inhibitor (Kohda et al, 1995). Some sulfated flavonoids in Polygonum hydropiper were discovered to show potent inhibition against bovine lens aldose reductase (Haraguchi et al, 1996). Other studies showed that flavonoid glycosides (Haraguchi et al, 1998), isoflavonoids (Jung et al, 2002), flavanone glucosides (myrciacitrins III) (Suryanarayana et al, 2004), protocatechualdehyde (Suryanarayana et al, 2002) and tannoid principles (Lee et al, 2005) had strong inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…2) Preliminary studies of flavones such as kaempferol and morin as well as the flavanones hesperitin and dihydroquercetin showed that they were converted to polar metabolites by this fungus, which were hydrolyzed by mild acid at room temperature to the respective substrates. The potential of flavonoid sulfates as therapeutically useful agents, 3,4) as standards to study flavonoid conjugation by mammals, 5) and for comparison with natural products 6) requires the preparation of flavonoids sulfated at specific sites.Chemical synthesis usually provides mixtures of flavonoid sulfates with sulfate groups randomly allocated 6) and may be difficult to purify. Thus the use of microorganisms to introduce sufalte groups at specific positions of the flavonoid nucleus seems interesting.…”
mentioning
confidence: 99%
“…2) Preliminary studies of flavones such as kaempferol and morin as well as the flavanones hesperitin and dihydroquercetin showed that they were converted to polar metabolites by this fungus, which were hydrolyzed by mild acid at room temperature to the respective substrates. The potential of flavonoid sulfates as therapeutically useful agents, 3,4) as standards to study flavonoid conjugation by mammals, 5) and for comparison with natural products 6) requires the preparation of flavonoids sulfated at specific sites.…”
mentioning
confidence: 99%